Does an aromatic chloride substitute position influence the aggregation properties of direct dyes? - Muntean Simona Gabriela; Grad Maria; Simu Georgeta-Maria; International Symposium on Analytical and Environmental Problems (17.) (2011) (Szeged) Szeged 2011. szeptember 19. (SZAB Szeged, 2012)
Dyes ions have a tendency to self-associate in aqueous solutions. The main factors influencing aggregation are dye concentration, electrolyte concentration, and temperature. In the present work, the influence of the chloride position in the dye structure on the dye aggregation was investigated. The molecular aggregation has been studied spectrophotometrically in aqueous solutions as a function of dye concentration (10'6 -s- 10"3 mol/L). As the concentration increases, different changes were observed in the dyes UV-vis spectra indicating that the molecules are beginning to aggregate. The shapes of the obtained spectra were totally different as the position of the chloride was changed in the dye molecule.
Keywords: Természettudományok; Kémiai tudományok